2023
DOI: 10.1200/jco.22.02894
|View full text |Cite
|
Sign up to set email alerts
|

Atezolizumab With or Without Radiotherapy for Advanced Squamous Cell Carcinoma of the Penis (The PERICLES Study): A Phase II Trial

Abstract: PURPOSE Patients with advanced penile squamous cell carcinoma have a poor prognosis (21% 2-year overall survival [OS] from diagnosis). We assessed the activity of atezolizumab (anti–PD-L1) in patients with advanced penile cancer, with or without radiotherapy (RT). PATIENTS AND METHODS A single-center, nonrandomized phase II study with two treatment arms was conducted in 32 patients with histologically confirmed advanced penile cancer. All patients received atezolizumab (1,200 mg) once every 3 weeks. Twenty pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In our study, we demonstrated the association between TCR clonality and the number of CD8 + T cells infiltrating into PSCC tissue. Since higher CD8 + T cell infiltration is associated with better clinical prognosis in patients with PSCC [ 6 , 44 ], TCR clonality may be an important biomarker for predicting the therapeutic response to immunotherapy in patients with PSCC, which needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we demonstrated the association between TCR clonality and the number of CD8 + T cells infiltrating into PSCC tissue. Since higher CD8 + T cell infiltration is associated with better clinical prognosis in patients with PSCC [ 6 , 44 ], TCR clonality may be an important biomarker for predicting the therapeutic response to immunotherapy in patients with PSCC, which needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although cisplatin-based chemotherapy offers better outcomes, long-term remission is rare, with overall survival lower than 12 months [ 5 ]. Significant response to immunotherapy with atezolizumab has been observed in a group of PSCC patients with high-risk human papillomavirus (HPV) and high infiltration of intratumoral CD3 + CD8 + T cells [ 6 ], evidencing the importance of tumor‑infiltrating T lymphocytes in PSCC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, no partial response was reported in 5 patients included in another study of nivolumab plus ipilimumab (2 stable disease and 3 progressive disease) . Atezolizumab was investigated as monotherapy or in combination with locoregional radiotherapy in a phase 2 trial including stage IV PSCC: the ORR was 44% with combination therapy and 17% with monotherapy . Finally, various ICI regimens tested in a heterogeneous population of chemotherapy-naive and chemotherapy-treated PSCC were included in a retrospective study sponsored by the Global Society of Rare Genitourinary Cancers: the pooled ORR was 13%, with a median progression-free survival of 3.2 months .…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary data for anti-PD(L)1 monotherapy trials reported an ORR of 14%-17%, including the first published dedicated prospective phase 2 study. 41,42 Basket studies testing combination immunotherapies have yielded preliminary data for subsets of patients with penile SCC. 43,44 Currently actionable genomic alterations appear rare in penile SCC.…”
Section: What Is the Optimal Systemic Therapeutic Regimen For Patient...mentioning
confidence: 99%